2020
DOI: 10.1002/eat.23349
|View full text |Cite
|
Sign up to set email alerts
|

Muscle dysmorphia: A systematic and meta‐analytic review of the literature to assess diagnostic validity

Abstract: Objective: Although muscle dysmorphia (MD) is a new addition to DSM-5 as a specifier of body dysmorphic disorder (BDD), previous studies have treated MD as a stand-alone diagnosis. We aimed to assess the validity of MD as a stand-alone diagnosis via systematic and meta-analytic review of MD literature using both Robins and Guze criteria and additional criteria from Kendler.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 77 publications
0
22
0
1
Order By: Relevance
“…Although some research has suggested muscle dysmorphia is a subtype of body dysmorphia [ 159 ], other research suggests strong similarities with anorexia nervosa, where pathological concern with muscle gain replaces pathological concern with weight loss [ 160 ]. Recent research suggests muscle dysmorphia may have validity for a stand-alone diagnosis [ 161 ].…”
Section: Recommendationsmentioning
confidence: 99%
“…Although some research has suggested muscle dysmorphia is a subtype of body dysmorphia [ 159 ], other research suggests strong similarities with anorexia nervosa, where pathological concern with muscle gain replaces pathological concern with weight loss [ 160 ]. Recent research suggests muscle dysmorphia may have validity for a stand-alone diagnosis [ 161 ].…”
Section: Recommendationsmentioning
confidence: 99%
“…Further, it has been suggested that the increasing amount of posts identified with the hashtag “fitspiration” (i.e., contents shared to promote healthy messages focused on fitness, exercise, eating styles, physical appearance, and weight control) can emphasize unrealistic body image as well as unattainable habits, thus leading to negative feelings in relation to mood, self-esteem, body image and emotional well-being [ 18 , 21 – 25 ]. This can also contribute [ 26 ] to induce in vulnerable users symptoms related to a specific form of body dysmorphic disorder (BDD), the so called muscle dysmorphia (MD), characterized by extreme preoccupation over one’s physical appearance and muscularity and by compulsive physical exercise [ 16 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Os resultados sobre os sintomas de ansiedade social estão de certa forma alinhados com os achados de Chandler et al (2009) que demonstrou que estes sintomas podem representar um fator motivacional subjacente aos sintomas de dm por meio do reforço negativo. O medo da avaliação negativa alheia, especialmente sobre o próprio físico, gerando um estado aversivo (Cooper, 2020;Eichstadt, 2020).…”
Section: Resultados E Discussão O Que é Dismorfia Muscular (Dm)?unclassified